The Crisis Within America's Military and the Struggle Between the Overseas and Guardian Paradigms - Thornhill, Paula G. (RAND Corporation, 2016)
The nation's understanding of both the common defense and organized violence has changed dramatically since 2001, and the diversification in the employment of violence produced a profound paradigm shift. This report is an attempt to start a conversation about how to better understand America's 21st-century military.